2016
DOI: 10.1134/s0006297916100205
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of minichromosome maintenance proteins inhibits foci forming of mediator of DNA-damage checkpoint 1 in response to DNA damage in human esophageal squamous cell carcinoma TE-1 cells

Abstract: Esophageal squamous cell carcinoma (ESCC) has a high morbidity in China and its treatment depends greatly on adjuvant chemotherapy. However, DNA damage repair in cancer cells severely affects the outcome of treatment. This study investigated the potential mechanism regarding mediator of DNA-damage checkpoint 1 (MDC1) and minichromosome maintenance proteins (MCMs) during DNA damage in ESCC. Recombinant vectors of MDC1 and MCMs with tags were constructed and transfected into human ESCC cell line TE-1. Immunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The research found MCM6 was an oncogene and could promote esophageal cancer cells proliferation 33 . Knockdown of MCM6 could significantly inhibit the forming of mediator of DNA-damage checkpoint 1, causing the DNA repair defects and decreased proliferation in esophageal cancer cells 33 , 34 . Our results were similar to their findings, unraveling the MCM6 was upregulated in EAC tissues and played an oncogenic role.…”
Section: Discussionmentioning
confidence: 99%
“…The research found MCM6 was an oncogene and could promote esophageal cancer cells proliferation 33 . Knockdown of MCM6 could significantly inhibit the forming of mediator of DNA-damage checkpoint 1, causing the DNA repair defects and decreased proliferation in esophageal cancer cells 33 , 34 . Our results were similar to their findings, unraveling the MCM6 was upregulated in EAC tissues and played an oncogenic role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MCM6 gene is involved in tumor pathogenesis 16 and promotes the progression of hepatocellular carcinoma (HCC) 14 . It also plays a vital role in cell proliferation, migration, invasion and the immune response in many cancer types, such as breast cancer 17 , 18 , HCC 16 , glioma 19 , esophageal squamous cell carcinoma (ESCC) 20 and endometrioid endometrial adenocarcinoma 21 . The MCM7 gene plays a significant role in eukaryotic DNA replication, and its overexpression is related to cellular proliferation and responsible for various cancers 22 .…”
Section: Introductionmentioning
confidence: 99%